Job Satisfaction of Nursing Students Working at a Pakistani Military Hospital in Lahore, Pakistan - Muhammad Ashraf Chaudhry, Noor ul Ain Lashari, Daniyal Asim Khan, Javaria Nosheen, Javed Rafique Malik, Ayesha Naveed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To assess overall job satisfaction of military student nurses in a tertiary care hospital in Lahore and to assess their satisfaction with salary, working environment, attitudes and behaviours of other healthcare professionals, patients and administration. Methodology: This analytical cross-sectional study was carried out at the Institute of Nursing at CMH Lahore Medical College from January to March 2022. Convenience sampling was used to select 152 nursing students enrolled at the college. A structured questionnaire was used to collect data on job satisfaction in terms of variables like satisfaction with salary, work environment, workload, attitude of healthcare professionals, patients, and management. SPSS 20 was used for data analysis. Results: Out of 152 nurses, the majority, 95 (62.5%) expressed overall job satisfaction, with 85 (55.9%) and 126 (82.8%) being satisfied with their salary and working environment respectively. The majority of nurses also expressed satisfaction with attitudes of healthcare professionals, patients, and administration. However, the majority had reservations over not getting enough time to rest and insufficient holidays. Conclusion: The majority of nurses from our study appeared satisfied with their job, salary, and overall working environment. The majority also expressed satisfaction with attitudes of their healthcare colleagues and patients. It is recommended to ensure better job satisfaction by reducing workload and providing entertainment facilities. Keywords: Job satisfaction, Nursing, Burnout